THE ROLE OF SCHOOLS IN PROMOTING LIFELONG HEALTH LITERACY: A COMPREHENSIVE REVIEW - Gowhar Ahmad Thoker; Professor Dharmendra Singh (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Health literacy, defined as the ability to access, understand, evaluate, and apply health information to make informed decisions, is a crucial skill for navigating modern healthcare systems and promoting personal well-being. Schools play a fundamental role in fostering health literacy among students, equipping them with the knowledge and skills necessary for a lifetime of informed health choices. This paper presents a comprehensive review of the literature on the role of schools in promoting lifelong health literacy. It examines various strategies, interventions, and curriculum approaches employed by schools to enhance health literacy among students. Additionally, it explores the challenges and opportunities associated with integrating health literacy education into school curricula and suggests recommendations for future research and practice in this area.